2015
DOI: 10.1189/jlb.2a0215-039rr
|View full text |Cite
|
Sign up to set email alerts
|

Teleost leukocyte immune-type receptors activate distinct phagocytic modes for target acquisition and engulfment

Abstract: Channel catfish (Ictalurus punctatus) IpLITRs belong to the Ig superfamily and regulate innate immune cell effector responses. This study tested the hypothesis that ITAM-dependent and ITAM-independent phagocytic pathways are engaged by different subtypes of the IpLITR family. When stably expressed in RBL-2H3 cells, the ITAM-containing fusion-construct IpLITR 2.6b/IpFcRγ-L stimulated phagocytic responses that were abrogated at suboptimal incubation temperatures and by pharmacological inhibitors of the classic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 69 publications
(106 reference statements)
2
34
0
Order By: Relevance
“…More recently, it was demonstrated that the inhibitory TS32.17 LITR 1.1b, which in addition to two ITIMs contains an atypical ITAM-like (ExxYx 2 Vx 16 Yx 2 V) sequence and an ITSM in its CYT, also mediated phagocytosis when expressed in rat basophilic leukemia-2H3 cells (39). Although both TS32.17 LITR1.1b and the chimeric activating LITR2.6b/IpFcRg-L receptors were shown to induce ERK1/2 and protein kinase B (Akt)-dependent signal transduction, there were differences in their signaling kinetics and sensitivity to pharmacological inhibitors (64). Combined, these experiments demonstrated a dual signal capability of TS32.17 LITR1.1b and further support the notion that different LITR isoforms may be involved in fine-tuning various immune response(s).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was demonstrated that the inhibitory TS32.17 LITR 1.1b, which in addition to two ITIMs contains an atypical ITAM-like (ExxYx 2 Vx 16 Yx 2 V) sequence and an ITSM in its CYT, also mediated phagocytosis when expressed in rat basophilic leukemia-2H3 cells (39). Although both TS32.17 LITR1.1b and the chimeric activating LITR2.6b/IpFcRg-L receptors were shown to induce ERK1/2 and protein kinase B (Akt)-dependent signal transduction, there were differences in their signaling kinetics and sensitivity to pharmacological inhibitors (64). Combined, these experiments demonstrated a dual signal capability of TS32.17 LITR1.1b and further support the notion that different LITR isoforms may be involved in fine-tuning various immune response(s).…”
Section: Discussionmentioning
confidence: 99%
“…Classically, the mediators recruited to FcR-FcRγ complexes include isoforms of PI3Ks, Vav, and Rho family GTPases [ 51 , 52 , 53 , 54 ]; in particular, Rac1 and Cdc42 dynamically control actin polymerization and are required for phagocytic cup formation as well as pseudopod extension [ 55 , 56 ]. Selective pharmacological inhibitors of these mediators were profiled in phagocytic assays in order to obtain detailed information regarding the biochemical pathways that facilitate IpLITR 2.6b/IpFcRγ-mediated phagocytosis and to compare these mechanisms with the classical mammalian FcR phagocytic mode [ 57 ]. Phagocytic activity was measured using a flow cytometric-based assay and 4.5 µm fluorescent polystyrene microsphere targets.…”
Section: Examination Of Stimulatory Iplitr-mediated Responsesmentioning
confidence: 99%
“…IpLITR 2.6b/IpFcRγ-L-mediated phagocytosis relied on a similar subset of intracellular effectors for target engulfment and was comparable to the ITAM- and SFK-dependent mode of phagocytosis utilized by mammalian FcRs [ 49 , 50 , 51 ]. Specifically, the IpLITR 2.6b/IpFcRγ-L phagocytic response was inhibited using small molecule inhibitors that targeted SFKs, Syk, PI3Ks, Cdc42, Rac1/2/3, phosphoinositide-dependent kinase 1 (PDK1), Akt, PKC, MEK1/2, and F-actin polymerization [ 57 ]. These data provide further biochemical details describing the phagocytic pathway engaged by a teleost immunoregulatory receptor.…”
Section: Examination Of Stimulatory Iplitr-mediated Responsesmentioning
confidence: 99%
See 2 more Smart Citations